The water dragon's bride. 11 - Toma, Rei; Lehrke, Abby (Shojo beat manga., 2019)
In the blink of an eye, a modern-day girl named Asahi is whisked away from her warm and happy home and stranded in a strange and mysterious world where she meets a water dragon god! Facing the gravity of his impending demise, the water dragon god vows that he will send Asahi back to her world before all his power disappears. As Asahi struggles to find a way to stay with him, she can<U+2019>t deny that the day when they must part is coming. Is it truly the end for these two star-crossed lovers?